Stepwise approach to continuous glucose monitoring interpretation for internists and family physicians. Issue 8 (17th November 2022) - Szmuilowicz, Emily D.; Aleppo, Grazia
ABSTRACT: Continuous glucose monitoring (CGM) use has expanded rapidly in recent years among people with both type 1 and type 2 diabetes. In concert with the globally increasing prevalence of type 2 diabetes, the majority of whom receive diabetes care from internists or family physicians rather than specialists, it is becoming increasingly incumbent upon physicians within internal medicine and family practice to interpret and utilize CGM data in real-world clinical practice. It is therefore of paramount importance that internists and family physicians have access to the tools which will enable them to (1) interpret CGM data, and (2) utilize CGM data to guide therapeutic modifications for their patients with type 2 diabetes. Given the limited amount of time available to internists and family physicians to address multiple complex topics in a typical office visit, a pragmatic, simple, and systematic approach to CGM interpretation is crucial. This article aims to provide internists and family physicians with a simplified and systematic approach to CGM interpretation that can be easily and efficiently implemented in a brief office visit. Plain Language Summary: Continuous glucose monitoring (CGM) allows people with diabetes to automatically monitor glucose levels throughout the day and night, helps them to make informed decisions about food choices and physical activity, and assists people with diabetes and their healthcare providers in adjusting diabetes medications. CGM use has increased greatly in recent years among people with both type 1 and type 2 diabetes. As the number of people with type 2 diabetes increases around the world, internists and family physicians increasingly need to understand CGM data and guide their patients who use CGM. As a result, internists and family physicians need to have the tools which will enable them to (1) interpret CGM data, and (2) use CGM data to help their patients adjust their diabetes therapies. Since internists and family physicians have limited time to address many medical issues in a typical office visit, a simple and systematic approach to CGM interpretation is needed. This article aims to provide internists and family physicians with a simple and orderly approach to CGM interpretation that can be easily and efficiently used in a brief office visit.